Reproductive cloning combined with genetic modification. Issue 11 (3rd November 2005) - Strong, C
Abstract : Although there is widespread opposition to reproductive cloning, some have argued that its use by infertile couples to have genetically related children would be ethically justifiable. Others have suggested that lesbian or gay couples might wish to use cloning to have genetically related children. Most of the main objections to human reproductive cloning are based on the child's lack of unique nuclear DNA. In the future, it may be possible safely to create children using cloning combined with genetic modifications, so that they have unique nuclear DNA. The genetic modifications could be aimed at giving such children genetic characteristics of both members of the couple concerned. Thus, cloning combined with genetic modification could be appealing to infertile, lesbian, or gay couples who seek genetically related children who have genetic characteristics of both members. In such scenarios, the various objections to human reproductive cloning that are based on the lack of genetic uniqueness would no longer be applicable. The author argues that it would be ethically justifiable for such couples to create children in this manner, assuming these techniques could be used safely.